Macroeconomic implications of the dynamics between power and trust: a theoretical formalisation of the `slippery slope' framework - Gaetano Lisi (Economics and Econometrics Research Institute (EERI), 2012)
This paper aims to provide a thorough theoretical formalisation of the `slippery slope' framework in order to highlight the effects and the macroeconomic implications of the dynamics between power and trust. In particular, the proposed model is able to differentiate between coercive and legitimate power, thus elucidating the dynamics between power and trust and its influence on tax climate and tax compliance. Also, by introducing trust in tax authorities as a determinant of tax compliance, the decision to under-report income is no longer based on expected profits maximisation and thus the tax compliance problem can not be explained by a pure economic approach. The main results of the model are the following: (i) trust-building actions are better than deterring measures for overall tax compliance, since they establish a cooperative tax climate and lead to a legitimate power, while too much power corrodes trust; (ii) in a society where trust is maximised and tax authority benefits from a legitimate power, both employment and economic growth are higher since tax evasion and shadow economy are lower and the level of taxation can be reduced.
Keywords: A12; A13; E26; H26; K34; K42; 330; trust (in) and power (of) tax authorities; tax compliance; tax evasion macroeconomics variables